The making of a WASP: Promises and realities of a nontraditional role - Kimberly A. Townsend (Adult Education Research Conference, 1994)
From 1942-1944 a controversial training program prepared women "to fly the Army way." But more than the development of cockpit skills is revealed through the voices of the women themselves who tell stories of personal development and a unique culture of women.